Look-angle-constrained control of arrival time with exact knowledge of time-to-go - Cho, Namhoon; Lee, Seokwon (AIAA, 2021)
The capability to control the time of arrival at a goal position as desired endows a single vehicle or a coalition of many of them with the strategic advantage to perform time-critical missions. Arrival time coordination can be used as an element to solve multi-agent, multidepot routing and task planning problems in cooperative unmanned aerial robots. The tactic known as Salvo, which either designates or synchronizes the impact times across multiple missiles to enhance their collective survivability as well as attack effectiveness, strongly depends on control of arrival time. In principle, control of arrival time is essentially adjustment of the arc length of the vehicle’s flight path through manipulation of the curvature, provided that most vehicles flying in the atmosphere often prefer not to change their speeds excessively. On the other hand, the capability to take measurements of the target with onboard sensors provides a higher degree of autonomy to the vehicle and hence allows a more intelligent behavior. Modern autonomous vehicles acquire information about the designated destination or the surrounding environment with imaging sensors, in particular. An onboard sensor that collects emission or reflection from the target is usually not likely to be omni-directional yet possesses only a finite field-of-regard. The requirement to ensure continuous acquisition of target-originated signals necessitates a measure to keep the information source inside the sensor’s field of view that spans over a solid angle of limited range. That is, a box constraint is imposed on the look angle.
Keywords: control of arrival time; biased proportional navigation guidance law (BPNG); pure proportional navigation guidance law (PPNG)